Formulation and evaluation of xanthan gum based aceclofenac tablets for colon targeted drug delivery (Brazilian Journal of Pharmaceutical Sciences, 2011)
The objective of the present study is to develop a colon targeted drug delivery systems for Aceclofenac using xanthan gum as a carrier. In this study, multilayer coated system that is resistant to gastric and small intestinal conditions but can be easily degraded by colonic bacterial enzymes was designed to achieve effective colon delivery of Aceclofenac. The xanthan gum, the drug and the physical mixture were characterized by Fourier transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC). All the formulations were evaluated for hardness, drug content uniformity and other physical properties. Release aspects of Aceclofenac in simulated gastrointestinal fluid and colonic fluid with enzymes were investigated. From these results, Eudragit coated system exhibited gastric and small intestinal resistance to the release of Aceclofenac. The rapid increase in release of Aceclofenac in SCF was revealed as due to the degradation of the xanthan gum membrane by bacterial enzymes. The designed system could be used potentially as a carrier for colon delivery of Aceclofenac by regulating drug release in stomach and the small intestine.